Prospective study of bone marrow in haematological disorders - Atla, Bhagya Lakshmi; Anem, Venkatalakshmi; Dasari, Anuradha (International Journal of Research in Medical Sciences, 2017)
Background: Bone marrow examination is useful in the diagnosis of both hematological and non-hematological disorders. The two most important techniques used for the diagnosis of hematological disorders are bone marrow aspiration and trephine biopsy which are complementary to each other. The present study is to evaluate the findings of bone marrow aspiration & trephine biopsy and their cytological and histological patterns in various hematological disorders. The aim of the study is to evaluate the clinical profile, spectrum, cytological and histological pattern of various hematological disorders reported in bone marrow aspiration and trephine biopsy respectively. Methods: It was a cross-sectional study design with 105 patients who underwent bone marrow examination for evaluation of hematological disorders in the Department of pathology, Andhra Medical College during the period of 2012 to 2014. Results: Among 105 cases studied, age of patients ranged from 1 to 68 yrs with mean age of 32.4 yrs and male predominance (1.5:1). Most of the patients presented with fever, shortness of breath, Easy fatigability and generalized weakness. The commonest physical findings were pallor followed by splenomegaly & hepatomegaly and in hematological parameters predominantly pancytopenia. Bone marrow aspiration was diagnostic in 53(50%) cases and trephine biopsy was diagnostic in 52(50%) cases. Anemias (50%) and leukemias (16%) are most common hematological disorders. Among the anemias, megaloblastic anemia is the most common (40%) cause of hematological non-malignancies. Among leukemias, acute myeloid leukemias are common cause of hematological malignancies. Conclusion: The present study showed the usefulness of bone marrow aspiration and trephine biopsy in evaluation of the bone marrow in routine haematological disorders and also for understanding disease progression, for diagnosis and therapeutic evaluation. These are also helpful in planning further investigation and management.